Apamin treatment accelerates equilibrium recovery and gaze stabilization in unilateral vestibular neurectomized cats: Cellular and behavioral aspects. (January 2019) - Tighilet, Brahim; Leonard, Jacques; Mourre, Christiane; Chabbert, Christian
Abstract: Sudden and complete unilateral loss of peripheral vestibular inputs evokes characteristic vestibular syndrome comprised of posturo-locomotor, oculomotor, vegetative and cognitive symptoms. Subsequently to the vestibular insult, a neurophysiological process called central vestibular compensation promotes the progressive restoration of the posture and balance. The modulation of the excitability of vestibular secondary neurons has been demonstrated to be a key process of this mechanism. However, the molecular mechanisms that support this modulatory process have thus far not been fully identified. The present study used a combination of a radio-labeled apamin binding experiment and a functional assessment of the vestibular function to demonstrate that unilateral vestibular neurectomy (UVN) induces both ipsi- and contralateral up-regulation of the apamin-sensitive calcium-activated small conductance K + (SK) channels, within the first days following the insult. We also demonstrate that apamin administration during the acute phase of the vestibular syndrome significantly reduces both the posturo-locomotor and vestibulo-ocular deficits induced by the UVN. This is illustrated by the reduction of both the spontaneous nystagmus and the static and dynamic balance unsteadiness. These data suggest that the regulation of SK channel expression may be part of the vestibular compensation process. It is also indicated that the pharmacological modulation of SK channels may be a potential way to alleviate the vestibular syndrome. Highlights: The study focuses on an animal model of unilateral permanent vestibular loss, the induced vestibular syndrome and the effects of pharmacological treatment with apamin. The originality of this approach relies on the use for the first time, of SK channels as pharmacological targets for antivertigo treatment. We show for the first time a substantial effect of apamin treatment at behavioral level, with significant attenuation of the acute vestibular syndrome and faster posturo locomotor recovery in vestibulo lesioned animals. We also demonstrate a regulation of SK channels that supports their direct involvement in both the alleviation of the vestibular syndrome and the functional recovery.